Survei status gross motor skill pada siswa kelas rendah di Sekolah Dasar Negeri Se-Kecamatan Wagir Kabupaten Malang - Yusdianto, Yusril; Wiguno, Lokananta Teguh Hari (Motion: Journal Research of Physical Education, 2024)
Students introduced to movement learning, including locomotor, non-locomotor, and manipulative learning, at the beginning of the school year through physical education. public's perception of today's educational landscape reveals that people think schools with an A accreditation are of a higher caliber than those with a lesser one. There has never been any research done on the gross motor skill level of low grade students at SDN Wagir District, Malang Regency, according to findings of interviews with PJOK teachers at the A-accredited school. Seeing that the gross motor skills of low class students were unknown, the researchers used this as the main background to determine the quality of students' motor skills in low class students at A-accredited SDN, Wagir District, Malang Regency. The aim of the research is to explain the level of gross motor skills of low grade students. This research concept uses a survey method combined with quantitative descriptive methods. With a sample size of 168 students, Gross Motor Development Test-2 (TGMD-2) was the instrument utilized. With a score of 90.0111, the study's findings indicate that low class students' gross motor skills fall into the average category. In the meantime, the standard deviation value received an 8.0230 score